These heathens : a novel - McKenzie, Mia; McKenzie, Mia (Random House, 2025)
"Where do you get an abortion in 1960 Georgia, especially if the town midwife goes to the same church as your parents? For seventeen-year-old Doris Steele, the answer is Atlanta, where her favorite teacher, Mrs. Lucas, calls upon her brash, wealthy childhood best friend, Sylvia, for help. While waiting to hear from the doctor who has agreed to do the procedure, Doris spends the weekend scandalized by, but drawn to, the people who move in and out of Sylvia's orbit: celebrities whom Doris has seen in the pages of Jet and Ebony, political leaders like Coretta Scott King and Diane Nash, women who dance close together, atheists! And even more shocking? Mrs. Lucas seems right at home. The young people Doris encounters are no less surprising. When he's not flirting too hard or talking too much, Sylvia's nephew, Dexter, brings Doris into the heart of Atlanta's civil rights movement, where some activists practice nonviolence to prepare for sit-ins, while others carry guns to protect Black families from the Klan. From the guests at a queer kickback to the student activists at a SNCC conference, Doris suddenly finds herself surrounded by so many people who seem to know exactly who or what they want. Doris knows she doesn't want a baby, but what does she want? Will this trip help her find out?"--